A qualitative study of the impact of the COVID‐19 pandemic on women seeking pelvic organ prolapse surgery in Alberta, Canada. (8th September 2022) - Knox, Erin; Ramage, Kaylee; Scime, Natalie; Ducey, Ariel; Brennand, Erin
Abstract: In addition to altering public infrastructure and social patterning, the COVID‐19 pandemic has delayed many pelvic organ prolapse (POP) surgeries. POP‐related stigma, symptomology and the experience of waiting for POP surgery can negatively impact women's quality of life and mental health. The experience of preoperative POP patients during the pandemic thus entails a new intersection of gendered, stigmatic and medical realities. Qualitative interviews were conducted with 26 preoperative POP patients as part of a larger qualitative study, 20 of whom spontaneously volunteered information about how the pandemic coloured their experience living with and awaiting surgery for POP. Interviews occurred between January and July 2021, which coincided with the second and third waves of the pandemic in Alberta, Canada, and before full immunisation was available for all Albertans. Pandemic‐related interview excerpts were thematically analysed, and four main findings emerged. (1) Though surgical delay meant living with unpleasant symptoms for longer than anticipated, some sought this out in order to protect vulnerable loved ones from possible hospital‐acquired infection, (2) shifting and unclear hospital policies and logistics resulted in intense preoperative stress, at times causing women to temporarily cease treatment, (3) decreased access to public restroom infrastructure caused women to reduce their outings and (4) the imperative to minimise social gatherings made it easier for women to engage in POP‐related, shame‐based self‐isolation without the notice of friends and family. As they can influence postoperative outcomes and treatment adherence, trends observed should be of interest to clinicians and policymakers alike.